Are pediatricians and otolaryngologists well prepared to identify early signs of vertical facial growth?. (April 2019) - Calvo-Henríquez, Christian; Martins-Neves, Silvia; Faraldo-García, Ana; Ruano-Ravina, Alberto; Rocha, Sofía; Mayo-Yáñez, Miguel; Martinez-Capoccioni, Gabriel
Abstract: Background: The prevalence of vertical facial growth is very high in the developed world. Most authors agree that mouth breathing is its main cause. Even though care is mainly conducted by odontologists, the professionals who first see these patients are pediatricians and otolaryngologists. The objective of this study is to analyze the ability of pediatricians and otolaryngologists to identify early signs of vertical facial growth among children. Methods: 60 participant aged 4.1–13.7 years were analyzed subjectively by 9 otolaryngologists, 9 pediatricians and two specialists in dentofacial orthopedics. They were also assessed objectively with cephalometric analysis. Results: Otolaryngologists showed 34.78% sensitivity, 92.86% specificity and 48.33% efficiency. Pediatricians showed 13.04% sensitivity, 100% specificity and 33.33% efficiency. Using a linear regression model compared against the objective measurements we found a weak positive correlation both for otolaryngologists and pediatricians. Conclusion: The sensitivity was very low for both groups. We believe it is of paramount importance to increase the awareness and the ability of otolaryngologists and pediatricians to recognize signs of disrupt facial growth.